Flash Card-Based Basic Throwing And Catching Movement Learning Model For Grade V Elementary School Students - Elma Maulida Wardhana; Sujarwo; Iwan Setiawan; Taufik Rihatno (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The basic movement of throwing and catching is one of the fundamental motor skills that must be mastered by students at the Elementary School level . This study aims to develop a flash card-based learning model for basic throwing and catching movements for fifth-grade elementary school students. This study uses the Research and Development (RnD) method that refers to the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) by involving 3 people as validators and 60 fifth-grade students as samples. Data collection was carried out through interviews, observations and tests. The results of the study showed that 21 models were considered feasible and able to improve the learning of basic throwing and catching movements in fifth-grade elementary school students as indicated by the results of the N-Gain Score test which was quite effective and the t-test with a sig. value of 0.00 <0.05 which showed a significant increase in learning basic throwing and catching movements based on flash cards in fifth-grade elementary school students. The recommendation in this study is that the throwing and catching activity can be designed with interesting variations, providing space for active student participation, and utilizing examples that are relevant to students' lives.